The Role of Classroom Contexts on Learners’ Grit and Foreign Language Anxiety: Online vs. Traditional Learning Environment - Zhao, Beibei (Frontiers in Psychology, 2022)
This review aimed at exploring the related investigations on the effects of online and traditional learning contexts on English as a foreign language (EFL) learners’ grit and foreign language anxiety (FLA). Studies have verified the relationship between learners’ grit and academic performance in online learning contexts. However, there is a need for studying the effect of face-to-face learning and face-to-screen learning on learners’ grit. On the other hand, studies have shown that classroom context is a mediating variable in the relationship between grit and FLA. Furthermore, few studies have been done on the effect of traditional classroom contexts and online learning contexts on learners’ FLA. Most studies showed that online learning contexts create more FLA. There are some reasons such as ambiguity of contexts, lack of feedback, lack of opportunities for communication, type of employed applications, cognitive load, technophobia, and reduction in enthusiasm which arouse learners’ anxiety in an online learning environment. In the end, the pedagogical implications are expounded to promote the learners’ grit and diminish anxiety for better performance. This review also provides some suggestions for further research to clarify our perspective on positive and negative emotional variables.